Prevalence of Nocturia in United States Women: Results From National Health and Nutrition Examination Survey. Issue 1 (January 2021) - Daugherty, Michael; Ginzburg, Natasha; Byler, Timothy
Abstract : Introduction: Nocturia can be one of the most bothersome lower urinary tract symptoms that can significantly affect quality of life. In both sexes, nocturia has been associated with decreased overall health. We aim to assess the prevalence of nocturia in US females and identify factors associated with significant nocturia. Methods: A cross-sectional, US population-based database (National Health and Nutrition Examination Survey) was queried for females surveyed during the years 2009 to 2014. Nocturia information was obtained from the question, "how many times do you urinate at night?" Significant nocturia was defined as those women who urinated 2 or more times per night. Demographic characteristics, information on urinary incontinence, and gynecologic/obstetrical history were analyzed. Multivariable logistic regression was performed to identify factors associated with significant nocturia. Results: A total of 7620 adult women were available for analysis. Of all women, 28.8% (95% confidence interval, 27.3–30.3) reported significant nocturia. Nocturia rates increased with increasing age ( P < 0.0001). For those women who underwent childbirth, delivery type had no association with nocturia ( P = 0.23). On multivariable analysis, only increasing age, black race, body mass index of 30 or greater, urge incontinence, and poor overall health were associated with increased rates of nocturia. Higher levels of education and increased household income were associated with lower rates of nocturia. Conclusions: Nocturia is prevalent in the United States with almost 30% of all women reporting significant nocturia. Importantly, nocturia does not affect only older individuals, as 1 in 6 women under the age of 40 years report waking 2 or more times per night to urinate.